Flexible and thermal-stable SiZrOC nanofiber membranes with low thermal conductivity at high-temperature. Issue 5 (May 2020) - Zhang, Xiaoshan; Wang, Bing; Wu, Nan; Han, Cheng; Wu, Chunzhi; Wang, Yingde
Abstract: Ceramic nanofibers with excellent thermal stability and low thermal conductivity are highly desired for high-temperature thermal insulation applications. However, the incompatibility of thermal stability and low thermal conductivity at high-temperatures largely limit the practical use of conventional single-phase ceramic nanofibers. Here, we report the preparation of multi-phase SiZrOC nanofiber membranes (NFMs) composed of amorphous SiOC and ZrO2 nanocrystals via electrospinning technique. The fabricated SiZrOC NFMs exhibited excellent high-temperature stability (∼1200 °C in Ar) and low thermal conductivity (∼0.1392 W m −1 K −1 at 1000 °C in N2 ). The decreased thermal conductivity is achieved through a synergistic mechanism, that the multi-phase interfaces and the ZrO2 nanocrystals create thermal transfer barriers to reduce the heat transfer, whilst the SiOC phase effectively suppresses radiative heat transfer. This unique combination of amorphous SiOC and ZrO2 nanocrystals provides a novel strategy to prepare high-performance thermal insulation materials, and the obtained SiZrOC NFMs are promising high-temperature thermal insulation materials.